The effect of subcutaneous methotrexate on markers of metabolic syndrome in psoriatic patients – preliminary report - Owczarczyk-Saczonek, Agnieszka; Drozdowski, Marek; Maciejewska-Radomska, Agata; Choszcz, Dariusz; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Methotrexate (MTX) has anti-proliferative and anti-inflammatory effects in psoriasis. Moreover, low doses can reduce the risk of developing cardiovascular diseases. It turns out that psoriasis and atherosclerosis have a similar pathogenetic mechanism: the same pro-inflammatory cytokines, Th1 and Th17, are involved in both diseases. Aim : To evaluate the effects of metabolic markers, protective cytokines (interleukin 10 (IL-10), transforming growth factor β (TGF-β)) and a marker of endothelial damage (endocan) in patients with plaque psoriasis. Material and methods : The study included 24 patients aged 27–69 years (9 female, 15 male) with plaque psoriasis. The metabolic syndrome according to the International Diabetes Federation (IDF) was evaluated. The laboratory tests were performed under fasting conditions: C-reactive protein (CRP), glucose, total cholesterol, triglycerides, high-density lipoprotein (HDL), uric acid, endocan, IL-10, and TGF-β. After 12 weeks of treatment with MTX injections 15 mg/week, every patient was assessed with the same laboratory tests. Results : After treatment we observed a statistically significant increase of endocan and IL-10, but no significant differences in the titer of TGF-β. C-reactive protein was reduced by approximately 54.7%. No improvement of lipid profile was observed, and even a significant increase in triglycerides was noted. Similarly, no significant difference was seen in the case of glucose and uric acid prior to and after treatment. Conclusions : Methotrexate in low doses in short-term treatment decreases CRP (anti-inflammatory effect) and increases endocan and IL-10 (potential protective role). Methotrexate is characterized by good efficacy and tolerability in therapy of patients with psoriasis.